Effect on immune response and virus shedding in the chicken vaccinated against inactivated local strain of Newcastle disease virus genotype VII - Nayan, Nursyuwari; Shohaimi, Syamsiah Aini; Ahmad Raus, Raha; Mat Yusof, Afzan; Ong, Geok Huai (Universiti Teknologi Malaysia, 2015)
The effectiveness of the new inactivated vaccine develop from local velogenic strain of Newcastle disease virus (NDV) Genotype VII and commercial vaccines LaSota were compared by determining the immune response and virus shedding of vaccinated chickens. Ten different groups of chicken consists of ten each, were vaccinated with and without adjuvant of the inactivated vaccine via intramuscular and subcutaneous, respectively. Three different adjuvants were used which include Oil-emulsion Complete Freund’s, Oil-emulsion Squalene-based, and aluminium hydroxide gel (Alum). As a comparison, a group of chicken was vaccinated with commercial vaccine and control group was not vaccinated. With 100% survival rate and highest mean haemaglutination-inhibition (HI) titre of log2 6, the inactivated vaccine with adjuvant Alum and Oil-emulsion Complete Freund’s surpassed the LaSota. In addition, the virus shedding was significantly reduced and comparable to LaSota vaccinated chicken. Whereas, without adjuvant, the chicken HI antibody titre is below log2 4 after vaccination and only 20-30% were survived. Based on the post-mortem findings on the survived chicken from each vaccinated group, their internal organs appeared normal and no sign of haemorrhage or pathognomonic signs of Newcastle disease (ND). Conclusively, vaccinated chicken are effectively protected from morbidity and mortality against virulent genotype VII challenge with the addition of adjuvant into inactivated local strain of NDV genotype VII vaccine. Thus, the development of inactivated local NDV genotype VII vaccine is a promising candidate to control the current ND endemic in Malaysia.